2009 35th Euromicro Conference on Software Engineering and Advanced Applications 2009
DOI: 10.1109/seaa.2009.74
|View full text |Cite
|
Sign up to set email alerts
|

Multi-layered Virtual Machines for Security Updates in Grid Environments

Abstract: Abstract-The use of user specific virtual machines (VMs) in Grid and Cloud computing reduces the administration overhead associated with manually installing required software for every user on every computational resource. However, a large number of user specific VMs increases the risk of security attacks. In particular, Cloud computing providers like Amazon suffer from these problems, since they offer different operating systems within VMs and delegate the security update problem for VMs to the users. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…These requirements are perfectly met by a union file system, as implemented, for example, by aufs or unionfs (which has been deprecated). Our previous work [13] showed that a union filesystem can be used as a root file system.…”
Section: A Multilayer Disk Imagesmentioning
confidence: 99%
“…These requirements are perfectly met by a union file system, as implemented, for example, by aufs or unionfs (which has been deprecated). Our previous work [13] showed that a union filesystem can be used as a root file system.…”
Section: A Multilayer Disk Imagesmentioning
confidence: 99%
“…While these solutions can be used to update dormant machines, they suffer from a potential compatibility problem. They "forcibly" install updates, either by changing an underlying layer [5] or by replacing files [4,6], and there is no guarantee that the updates can be safely applied and that they are compatible to the software stack and the configuration of all affected virtual machines.…”
Section: Introductionmentioning
confidence: 99%
“…In our system architecture, a VD is built from a shared golden image from the OS database, merged with personal settings, for example by using a copy-on-write solution with unionFS. Schwarzkopf et al show how multi-layer VDs simplify the complexity of upgrading the golden image without causing broken dependencies and/or conflicts [3]. To improve the usability of DaaS, combining DaaS with application virtualization technologies such as Softricity and Microsoft App-V is very promising.…”
Section: Introductionmentioning
confidence: 99%